Species of Bicellaria (Diptera: Hybotidae) from Asia - Barták, Miroslav; Plant, Adrian; Kubík, Štěpán (Zootaxa, 2013)
Bicellaria amankutanensis sp. nov. (Uzbekistan), B. chimganensis sp. nov. (Uzbekistan), B. farkaci sp. nov. (China), B. globulicauda sp. nov. (Uzbekistan), B. koreana sp. nov. (North Korea, Russia), B. kovalevi sp. nov. (Georgia), B. setitibia sp. nov. (Georgia), B. shatalkini sp. nov. (Russia), B. thailandica sp. nov. (Thailand), and B. woodi sp. nov. (Japan) are described and illustrated. Bicellaria montana Kato is newly synonymised with B. uvens Melander. Bicellaria spuria ingrata Collin is considered a distinct species. A key to all known Asian species of Bicellaria is provided.